Health-related quality of life in older people with osteoporotic vertebral fractures: a systematic review and meta-analysis. Issue 10 (October 2016) - Al-Sari, U.; Tobias, J.; Clark, E.
Abstract Health-related quality of life in osteoporotic patients with vertebral fracture is of increasing interest, but relevant studies have yielded debatable results. This systematic review and meta-analysis of 16 observational studies demonstrate a clear association between physical health status and presence of vertebral fracture after accounting for age. This meta-analysis was conducted to identify if there are any differences between physical and/or mental health-related quality of life (HRQoL) in older people with osteoporosis based on conventional T-score definitions and the presence or absence of vertebral fracture. A comprehensive search was undertaken using the databases of PubMed, Embase, Medline, Web of Science, and the "grey" literature from 1950 to the end of April 2015. Search terms for vertebral fracture (VF) included VF, osteoporotic fracture, fragility fracture, and spinal fracture. Quality of life was searched using the following terms: quality of life, health-related quality of life, HRQoL, and QoL. Strict inclusion and exclusion criteria were used. The standardized mean difference (SMD) was calculated for each HRQoL domain by the difference in means between case and control groups divided by the pooled SD of participants. Sixteen eligible studies were identified involving 3131 men and women. There was evidence of publication bias and heterogeneity. The meta-analysis showed worse physical (SMD = 0.53, 95 % confidence interval (CI) 0.38 to 0.68;P  < 0.001) and mental (SMD = 0.19, 95 % CI 0.05 to 0.33;P  = 0.009) HRQoL in osteoporotic older people with vertebral fracture compared to those without fracture. Similar differences were observed for physical HRQoL in further analyses accounting for possible confounding effects of age. Sub-analysis to assess associations between number/severity of fractures and time since fracture was not possible due to small numbers of studies that accounted for age. Osteoporotic older people with vertebral fracture have worse physical HRQoL than osteoporotic older people without vertebral fracture, even after accounting for age differences.